Women’s Inclusion in India: Constitutional and Legislative frameworks - Choudhury, Kisholoy (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Indian Constitution lays the foundation for gender equality and women’s empowerment through a range of fundamental rights and directive principles. Over the years, India has developed a strong legislative and institutional framework to support women’s inclusion in all aspects of public and private life. This paper explores constitutional provisions, key laws enacted by legislature, policies, and institutional mechanisms promoting women’s rights and gender equality. It further analyzes the progress made, persistent barriers to effective implementation, and strategies to bridge the gap between law and practice. The study adopts a doctrinal and analytical approach, relying on constitutional texts, statutes, case laws, policy documents, and secondary literature. It argues that while India has made considerable progress in establishing a legal foundation for women’s empowerment, systemic, social, and structural changes are essential to translate legal commitments into the practical benefits for all women.